Pemanfaatan Media Sosial Terhadap Pengetahuan Remaja Tentang Kesehatan Reproduksi Di Desa Tijayan - Fatya Nurul Hanifa; Zesika Intan Navelia; Novita Puspita Dewi (Borneo Nursing Journal (BNJ), 2026)
Introduction: Adolescents are an age group that is vulnerable to reproductive health problems due to limited accurate and reliable information. Along with the development of digital technology, social media has become one of the main means for adolescents to obtain information, including related to reproductive health. Implementation: This study aims to determine the relationship between social media utilization and the level of reproductive health knowledge among adolescents in Tijayan Village, Klaten Regency. Research methods: This study used a descriptive quantitative approach with a cross-sectional design. The research sample was 90 adolescents aged 15-23 years who were taken with total sampling technique. Instruments in the form of questionnaires. Data analysis used Spearman correlation test with a significance level of 0.05. Results: Most respondents utilize Instagram (42%), TikTok (33%), and YouTube (25%) as sources of reproductive health information. The level of knowledge of respondents was mostly in the good (46%) and sufficient (40%) categories. The Spearman test results showed that there was a significant relationship between social media utilization and the level of reproductive health knowledge (ρ = 0.212; p = 0.044). Conclusion: There is a significant relationship between social media utilization and the level of reproductive health knowledge in adolescents. Social media can be used as a potential educational tool to increase adolescents' understanding of reproductive health issues in adolescents.